SUPPLY CHAIN UNCERTAINTY: AN EMPIRICAL STUDY OF INDONESIA’S AGRO-INDUSTRY - Yandra Rahadian Perdana (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Supply chain management (SCM) is a multi-stakeholder network for managing the flow of raw materials, finished products, information and money. The supply chain’s network refers to the interdependencies of the processes and activities. Taking this into account, stakeholders deal with an environment of volatility, uncertainty, complexity and ambiguity (VUCA). The dynamic nature of the supply chain’s environment implies uncertainty in the upstream and downstream sides. Drawing from the literature, manufacturers need to mitigate any uncertainty in their supply chains, which can consist of supply, demand, and technology uncertainties. However, the previous literature neglected any discussion of supply chain uncertainty in the context of the agro-industry. Hence, to answer this gap, this study aimed to investigate the supply chain’s environmental uncertainty factors in the agro-industry’s sectors. Accordingly, this study obtained 30 respondents from the agro-industry in Indonesia. This study reported that the agro-industry in Indonesia has uncertainties about supply, demand and technology. It is faced with the inability of suppliers to consistently deliver raw materials, in terms of their quantity and quality. Meanwhile, demand uncertainty is caused by the fluctuations in customers’ demands and the industry’s low forecasting accuracy. Moreover, the rapidly changing technology has implications for uncertainty in services and product standards; making it difficult for manufacturers to anticipate the changes. This uncertainty in the supply chain’s environment needs to be controlled by the agro-industry through supply chain integration